Exposure to perchlorate, nitrate and thiocyanate was associated with the prevalence of hypertension - Xiaofan Miao; Yan Chen; Jingping Lu; Hongjian Shan; Ran Chen (BMC Cardiovascular Disorders)
Abstract Background Our study aims to examinate the relationships between exposure to perchlorate, nitrate, and thiocyanate and the risk of hypertension. Methods A total of 21,321 participants were selected from the National Health and Nutritional Examination Survey (NHANES). We used logistic regressions models to explore the odds ratio of urinary perchlorate, nitrate, and thiocyanate on the risk of hypertension and restricted cubic splines to check the nonlinearity. Results 2851 (13.4%) individuals were diagnosed with hypertension. Multivariable logistic regression analysis suggested that urinary perchlorate and nitrate were inversely associated with hypertension, and thiocyanate has a positive correlation. Compared with the lowest quartile, the highest quartile of odds ratios was 0.86 (0.74–1.00; P = 0.048) for perchlorate, 0.79 (0.67–0.94; P = 0.007) for nitrate, and 1.47 (1.25–1.73; P < 0.001) for thiocyanate. Restricted cubic splines showed that urinary perchlorate was nonlinearly associated with hypertension (P = 0.0014). Conclusions Higher exposure to perchlorate and nitrate were associated with a lower risk of hypertension, while a positive association was observed for urinary thiocyanate.